Meguru Panggul and Meguru Kuping; The Method of Learning and Teaching Balinese Gamelan - I Wayan Sudirana (Institut Seni Indonesia Denpasar, 2018)
â€œTrue musical experience is the experience of trustâ€â€”trust between the student and teacher. Whatever teaching method a teacher applies, it will not work without any trust. â€œIt is only when we learn to trust one another, to dissolve in the realization of our shared humanity, will the music finally play.â€ This is an autoethnography. It exhibits the long process of musicianship in a traditional Balinese community. Also, I explore how, as a modern Balinese musician, my musicianship fit in with the new musical setting of a Western community. The paper is divided into three parts: the first part is an exploration of the traditional learning process and Balinese musical pedagogy called meguru panggul. The second is an exploration of my experience in continuing my studies at ISI Denpasar (the Balinese Arts Institute)â€” how the teacher conducts the learning process in a formal setting, and my own discovery in learning with ear (meguru kuping). And lastly, the third explores the development of my perception and conception of a new learning and teaching style, when I was exposed to the Western way of teaching and learning music at the University of British Columbia, Vancouver, Canada.